Cocoa's Potential as Functional Food for Diabetes Glucose Management - Maulana, Ginata Ayu; Rahmawati, Irma Sarita; Fibrianto, Kiki (Jurnal Gizi dan Dietetik Indonesia (Indonesian Journal of Nutrition and Dietetics), 2026)
Background: Diabetes mellitus (DM) is a metabolic disorder characterized by chronic hyperglycemia due to impaired insulin secretion or function, and its management relies heavily on drug therapy and lifestyle modifications, which are often challenging to maintain consistently. Therefore, more effective alternatives, such as functional foods like cocoa, which contains various bioactive compounds that may play a role in blood glucose regulation, are needed.Objectives: This literature review aims to explore the potential of cocoa as a functional food for blood glucose management in diabetic patients based on existing scientific evidence.Methods: This study is a systematic literature review conducted by searching the Web of Science, Scopus, and PubMed databases within the period of 2015–2025. The analyzed articles include in vivo studies on diabetic animal models, meta-analyses, and clinical trials in humans related to cocoa consumption and its effects on diabetes parameters.Results: In vivo studies show that a flavanol-rich cocoa diet improves insulin sensitivity, reduces HbA1c levels, and protects endothelial and pancreatic cells from oxidative stress. Meta-analyses of clinical trials indicate that cocoa flavanol supplementation (200-600 mg/day) significantly reduces HOMA-IR, triglycerides, and inflammation. Observational studies also suggest that moderate chocolate consumption may reduce the risk of type 2 diabetes.Conclusions: Cocoa has the potential to serve as a functional food for blood glucose management through improved insulin sensitivity, antioxidant effects, and gut microbiota modulation. However, further large-scale clinical trials are needed to determine the optimal dosage and long-term efficacy of cocoa in diabetes prevention and management.